EFFECT OF COMPREHENSIVE DENTAL TREATMENT UNDER GENERAL ANAESTHESIA ON CHILDREN’S ORAL-HEALTH-RELATED QUALITY OF LIFE: A COMPARATIVE CROSS-SECTIONAL STUDY - Qazi, Halima Sadia; Usman Nazir; Hira Nisar; Omer Ali; Palwasha Babar; Sajjad Ahmad (Journal of Ayub Medical College Abbottabad, 2024)
Background: Despite reductions in dental caries experience in developed countries, early childhood caries remains the most prevalent health problem in developing countries. This has a direct impact on the oral health-related quality of life of both children and parents. The objective of this study was to examine the impact of comprehensive dental treatment under general anaesthesia on Oral health-related quality of life in children, using a parental and caregiver perception questionnaire. Methods: A comparative study was conducted in the Children Hospital, Pakistan Institute of Medical Sciences, Islamabad from July to December 2015. A total of 40 children were enrolled in the study. The oral health-related quality of life questionnaire was completed by either parent/caregiver at the initial and follow-up visits after 4-8 weeks of treatment under general anaesthesia. Results: The mean age of all the enrolled children was 5.7±1.7 years. Among 40 children, 55% (22) were girls and 45% (18) were boys. A highly significant reduction was observed between the pre and post-treatment P-CPQ total scores from 76.9±15.8 to 13.3±9.5 with a p-value <0.0001. Regarding the P-CPQ domains, a significant reduction from the pre- to post-treatment scores was observed for oral symptoms; functional limitations, emotional well-being, and social well-being with a p-value <0.0001. Conclusion: The oral health-related quality of life was significantly improved after comprehensive treatment under GA. The findings of this study may be utilized to improve future guidelines and betterment of dental health of children by health care providers and initiatives for future health programs.